Edible Insects Consumption in Africa towards Environmental Health and Sustainable Food Systems: A Bibliometric Study - Newton R. Matandirotya; Walter Leal Filho; Gaathier Mahed; Basil Maseko; Cleophas V. Murandu (MDPI, 2022)
Africa is home to an estimated wild edible insect population of 1000 species that offer an opportunity for sustainable food systems while also improving food and nutrition security on the continent. Edible insect consumption has been part of African communities for a long time and forms part of their diets and cuisines, particularly within low-income households with limited resources. The purpose of our study was to investigate and review the contribution that edible insects can make towards the realisation of sustainable food systems, and environmental/planetary health including the fulfilment of Sustainable Development Goal number 2 (zero hunger). Our study applied a bibliometric analysis approach using VOS Viewer, a data mining software. The study established that the consumption of edible insects is still widespread across many African countries and therefore can be used as an avenue for improving environmental health and enhancing food systems on the continent through a reduction in meat-based diets. This, in the long term, will also reduce the emission of greenhouse gases such as carbon dioxide and methane from livestock production-related activities. Edible insects are also known to contain a high percentage nutrient content of proteins, fats and iron and, thus, can also play a vital role in reducing food insecurity and malnutrition, particularly within low-income households. Due to the existence of a high number of edible insect species on the continent, communities in Africa can easily access sources that can further be preserved using various indigenous techniques while also having minimal impact on the environment. In addition, being a source of nutritious food, edible insects can also be a source of establishing sustainable livelihoods, as well as being able to be commercialised, thus further creating employment opportunities and economic growth. Some of the notable edible insects in abundance on the continent include termites, ants, crickets and caterpillars. Our study recommends that Africa should commercialise edible insect production, in addition to preservation processing that leads to the eradication of perennial food insecurity and malnutrition and improves environmental health, as well as developing sustainable food systems. We also further recommend the establishment of food safety guidelines on edible insects as most African countries do not have such a plan in place currently.